Does Characteristics Of The Board Of Commissoners Affect Earning Persistance? - Pratomo, Dudi; Rotua, Grace Yohana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The board of commissioners is one of the elements that must be present in a public company. This study aims to analyze the influence of the board of commissioners' characteristics on public companies' earnings persistence. The research period is 2017-2021, with a research sample of 16 companies in the food and beverage sector. The dependent variable of the research is earnings persistence, with the independent variable, as the completeness of this study using control variables. The results showed that the common effect model was the best in interpreting the impact of the influence of the Board of Commissioners on earnings persistence from the four characteristics of the Board of Commissioners that had been examined. It was found that the variable number of Board of Commissioners meetings had a significant positive effect on earnings persistence, while the variable had no significant effect. These findings suggest that the more and the quality of the number of meetings held by the board of commissioners will result in better earnings persistence. Another interesting finding is that the number of independent commissioners, expertise, and gender does not affect earnings persistence.